2010
DOI: 10.1074/jbc.m110.124958
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Lung Cancer Cell Migration and Invasion by Reactive Oxygen Species and Caveolin-1

Abstract: The acquired capability of tumor cells to migrate and invade neighboring tissues is associated with high metastatic potential and advanced stage of cancers. Recently, signaling molecules such as reactive oxygen species (ROS) and caveolin-1 (Cav-1) have been implicated in the aggressive behavior of cancer cells. However, the roles of specific ROS in cancer cell migration and Cav-1 regulation are unclear. We demonstrate here that Cav-1 plays an important role in the migration and invasion of human lung carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
171
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(176 citation statements)
references
References 57 publications
5
171
0
Order By: Relevance
“…Ho et al found that 0.1-5 μΜ H 2 O 2 increased the number of invading colorectal cancer cells SW620 (Ho et al, 2011). But the migration is inhibited by 100 μΜ H 2 O 2 in lung cancer cells H460 (Luanpitpong et al, 2010). In this study, we showed that 10 μΜ H 2 O 2 promoted migration, whereas higher concentrations from 50 μΜ to 200 μΜ suppressed migration of breast cancer cells MDA-MB-231 in a dosedependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…Ho et al found that 0.1-5 μΜ H 2 O 2 increased the number of invading colorectal cancer cells SW620 (Ho et al, 2011). But the migration is inhibited by 100 μΜ H 2 O 2 in lung cancer cells H460 (Luanpitpong et al, 2010). In this study, we showed that 10 μΜ H 2 O 2 promoted migration, whereas higher concentrations from 50 μΜ to 200 μΜ suppressed migration of breast cancer cells MDA-MB-231 in a dosedependent manner.…”
Section: Discussionsupporting
confidence: 54%
“…Additional mutations have been described in breast cancer since then [39]. Also, Caveolin-1 expression is regulated at the posttranscriptional level in a differential manner by ROS species and subsequent proteasome-mediated degradation [40]. To what extent this might be a relevant mechanism in the tumor environment remains to be established.…”
Section: The Tumor Suppressor Hypothesismentioning
confidence: 99%
“…Furthermore, PPP maintains cellular redox status by providing a reduced form of glutathione which removes reactive oxygen species (ROS). Although the generation of ROS is an indication of cell death or induction of gene variation (mutation), ROS are also signaling molecules that are useful in the manipulation of cellular migration [3][4][5][6] . The generation of lactic acid is very helpful in allowing the progression of metastasis.…”
Section: Introductionmentioning
confidence: 99%